Integrating research into language teaching: Beliefs and perceptions of university teachers. Issue 5 (3rd September 2019) - Hu, Yanjuan; van der Rijst, Roeland M.; van Veen, Klaas; Verloop, Nico
ABSTRACT: Internationally, universities and policy-makers are calling for stronger integration of research into teaching. However, it is unclear how to implement this in practice in different disciplinary areas and contexts. This study contributes to this understanding with a focus on language teaching in the Chinese context. We surveyed 152 university teachers regarding their beliefs about and their perceived actual integration of research in their teaching practice. The teachers highly valued integration of research in teaching in an ideal situation but perceived low integration of research into their actual teaching practice. This gap was smaller for teachers from research-intensive universities and for those who had more research experience and spent more than 25% of their work time on research. Other reasons for this gap included fixed curricula, heavy teaching tasks, lack of student motivation and difficulties reconciling integration of research into teaching with the institutional aim of improving students' language proficiency.